Improved oxidation stability and crosslink density of chemically crosslinked ultrahigh molecular weight polyethylene using the antioxidant synergy for artificial joints. Issue 1 (9th July 2022) - Shah, Nouman Ali; Lan, Ri‐Tong; Dai, Rui; Jiang, Kai; Shen, Hui‐Yuan; Hong, Rui; Xu, Jia‐Zhuang; Li, Lingli; Li, Zhong‐Ming
Abstract: Vitamin E (VE) is currently an approved antioxidant to improve the oxidation stability of highly crosslinked ultrahigh molecular weight polyethylene (UHMWPE) insert used commercially in total joint arthroplasty. However, the decrease in crosslink density caused by VE reduces wear resistance of UHMWPE, showing an uncoordinated challenge. In this work, we hypothesized that D‐sorbitol (DS) as a secondary antioxidant can improve the antioxidant efficacy of VE on chemically crosslinked UHMWPE. The combined effect of VE and DS on oxidation stability of UHMWPE was investigated at a set of controlled hybrid antioxidant content. The hybrid antioxidant strategy showed significantly synergistic enhancement on the oxidation stability of chemically crosslinked UHMWPE compared with the single VE strategy. More strikingly, the crosslink density of the blends with hybrid antioxidants stayed at a high level since DS is not sensitive to crosslinking. The relationships between oxidation stability, mechanical properties, crosslink density, and crystallinity were investigated, by which the clinically relevant overall performance of UHMWPE was optimized. This work provides a leading‐edge design mean for the development of joint bearings. Abstract : Hybrid VE and DS synergistically enhance the oxidative stability of chemically crosslinked UHMWPE and maintain higher crosslink density than single VE.